Viral RNA trafficking is inhibited in replicase-mediated resistant transgenic tobacco plants. - Nguyen, L (1996)
Transgenic tobacco (Nicotiana tabacum cv. Turkish Samsun NN) plants expressing a truncated replicase gene sequence from RNA-2 of strain Fny of cucumber mosaic virus (CMV) are resistant to systemic CMV disease. This is due to suppression of virus replication and cell-to-cell movement in the inoculated leaves of these plants. In this study, microinjection protocols were used to directly examine cell-to-cell trafficking of CMV viral RNA in these resistant plants. CMV RNA fluorescently labeled with the nucleotide-specific TOTO-1 iodide dye, when coinjected with unlabeled CMV 3a movement protein (MP), moved rapidly into the surrounding mesophyll cells in mature tobacco leaves of vector control and untransformed plants. Such trafficking required the presence of functional CMV 3a MP. In contrast, coinjection of CMV 3a MP and CMV TOTO-RNA failed to move in transgenic resistant plants expressing the CMV truncated replicase gene. Furthermore, coinjection of 9.4-kDa fluorescein-conjugated dextran (F-dextran) along with unlabeled CMV 3a MP resulted in cell-to-cell movement of the F-dextran in control plants, but not in the transgenic plants. Similar results were obtained with viral RNA when the 30-kDa MP of tobacco mosaic virus (TMV) was coinjected with TMV TOTO-RNA into replicase-resistant transgenic tobacco expressing the 54-kDa gene sequence of TMV. However, in these transgenic plants, the TMV-MP was still capable of mediating cell-to-cell movement of itself and the 9.4-kDa F-dextran. These results indicate that an inhibition of cell-to-cell viral RNA trafficking is correlated with replicase-mediated resistance. This raises the possibility that the RNA-2 product is potentially involved in the regulation of cell-to-cell movement of viral infectious material during CMV replication.